Applications of dust explosion hazard and disaster prevention technology. (November 2020) - Wei, Min-Chi; Cheng, Yu-Chi; Lin, Yong-Ye; Kuo, Wen-Kai; Shu, Chi-Min
Abstract: Powdered materials are widely used in industrial processes, chemical processing, and nanoscience. Because most flammable powders and chemicals are not pure substances, their flammability and self-heating characteristics cannot be accurately identified using safety data sheets. Therefore, site staff can easily underestimate the risks they pose. Flammable dust accidents are frequent and force industrial process managers to pay attention to the characteristics of flammable powders and create inherently safer designs. This study verified that although the flammable powders used by petrochemical plants have been tested, some powders have different minimum ignition energies ( MIEs ) before and after drying, whereas some of the powders are released of flammable gases. These hazard characteristics are usually neglected, leading to the neglect of preventive parameters for fires and explosions, such as dust particle size specified by NFPA-654, MIE, the minimum ignition temperature of the dust cloud, the minimum ignition temperature of the dust layer, and limiting oxygen concentration. Unless these parameters are fully integrated into process hazard analysis and process safety management, the risks cannot be fully identified, and the reliability of process hazard analysis cannot be improved to facilitate the development of appropriate countermeasures. Preventing the underestimation of process risk severity due to the fire and explosion parameters of unknown flammable dusts and overestimation of existing safety measures is crucial for effective accident prevention. Highlights: The imperfect of PSI is the main reason for the continuous occurrence of dust accidents. Dust hazard characteristic parameters are important PSI for the implementation of PHA. Create a safety management framework and standard for flammable dust workplaces. The most non-compliant factor found in dusty locations is explosion-proof electrical equipment wrong choice. Lack of verified dust hazard characteristics parameters lead to underestimation of process risk.